Fixation-related potentials in visual search: A combined EEG and eye tracking study - Kamienkowski, Juan Esteban (2012)
We report a study of concurrent eye movements and electroencephalographic (EEG) recordings while subjects freely explored a search array looking for hidden targets. We describe a sequence of fixation-event related potentials (fERPs) that unfolds during ̃ 400 ms following each fixation. This sequence highly resembles the event-related responses in a replay experiment, in which subjects kept fixation while a sequence of images occurred around the fovea simulating the spatial and temporal patterns during the free viewing experiment. Similar responses were also observed in a second control experiment where the appearance of stimuli was controlled by the experimenters and presented at the center of the screen. We also observed a relatively early component (̃150 ms) that distinguished between targets and distractors only in the freeviewing condition. We present a novel approach to match the critical properties of two conditions (targets/distractors), which can be readily adapted to other paradigms to investigate EEG components during free eye-movements. © 2012 ARVO.